An investigation of school gardens in the curriculum: recontextualising the biodiversity discourse in the national curriculum statement: a case of Mount Zion Junior Secondary School - Tundzi, Kenneth Simphiwe Vuyisa (Rhodes University, Faculty of Education, Department of Education, 2009)
With the dawning of a new era in South African politics in 1994 it became evident that education was going to be re-organised along with other government structures in South Africa. I begin the study by reviewing this curriculum change in South Africa that has taken place since 1995. This involved the development Curriculum 2005 (C2005) and the subsequent revision of C2005, which is now the National Curriculum Statement (NCS). This curriculum introduced an environmental focus into all the Learning Areas, which gave teachers a mandate not only to teach about environmental concepts and issues (such as biodiversity) at schools but to also address them in the communities outside the schools. This study considers biodiversity issues as biodiversity is a new focus in South African policy more broadly, and particularly in the Natural Science Learning Area. Our school has received vegetable and indigenous plant gardens from the South African National Biodiversity Institute, which provides a rich new resource for teaching about biodiversity, particularly in the Natural Sciences. My interest in the study was to investigate how schools (teachers) can use school gardens in the recontextualisation of the National Curriculum Statements focusing on the Natural Science Learning Area in Grade 7 at my school. I used Bernstein's (1990) concepts of delocation, relocation, ideological transformation and selective appropriation and Cornbleth's (1990) theory of curriculum contextualization to understand and interpret the recontextualisation process in the four lessons studied. In this research I was involved in the planning of the lessons with the Grade 7 Natural Science teacher. I taught one lesson as a demonstration and then observed while the teacher taught the other three lessons. I conducted this study as an action research case study. I used focus group interviews, classroom observations, document analysis and interviews as methods of data collection. The study found that the use of school gardens for teaching biodiversity can help with the recontextualisation of NCS in schools, and for the teaching of biodiversity, but that there is a need to understand and address various recontextualisation issues if this is to be done effectively. The study revealed that use of the school gardens for learning about biodiversity in the NS Learning Area is influenced by teachers' knowledge, experience, teaching styles and available resources, as well as management issues and the complexity of the NCS discourse itself. The study also revealed that socio-cultural and structural factors (e.g. language and class size) also affect how biodiversity is taught in schools, and thus how the recontextualisation of the NCS takes place. The study concludes by making recommendations for taking this work forward in the context of our school as it addresses the gap that exists between policy and practice.
Keywords: South African National Biodiversity Institute; Curriculum change -- South Africa -- Case studies; Environmental education -- Curricula -- South Africa -- Case studies; School gardens -- South Africa -- Case studies; Science -- Study and teaching (Secondary) -- South Africa -- Case studies; Teacher participation in curriculum planning -- South Africa -- Case studies; Educational change -- South Africa -- Case studies; Education -- South Africa -- Curricula; Education and state -- South Africa